Applications of Subordination for Holomorphic Functions Stated by Generalized By-Product Operator - Mustafa I. Hameed; Shaheed Jameel Al-Dulaimi; Hussaini Joshua; Ismael I. Hameed; Israa A. Ibrahim; Kayode Oshinubi (International Journal of Mathematics and Mathematical Sciences)
The aim of this research is to investigate certain problems of differential subordination and superordination of analytic univalent functions in an open unit disk. Furthermore, the universal by-product operator and geometric properties such as coefficient inequalities are investigated. Remarkable results on the differential subordination and superordination of analytic univalent functions and results using higher derivative operator for differential subordination are obtained. Some interesting applications of subordination in the unit disk are obtained using convolution and convexity.